(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Ecological Landscape is a method of organizing the building’s and maintaining the ground landscaping that considers the ecology of the site creates gardens and parks that enhance the surrounding landscape for the benefit of humans and all other organisms’ life in the ecosystem. Therefore, to build an eco-landscape and sustainable urban design, these challenges need to be faced with efficient and creative ideas and hard efforts to succeed. The paper focuses on the environmental issues, investigates and works on the development of old military sites and camps, which is destroyed by the 2011 war in Tripoli, to re- functioning and developing them as entertaining places and open public green spaces for people. Therefore, these sites have been taken as a case study of the paper, to integrate them within the urban land use planning of the city of Tripoli, considering the idea of eco-sustainable landscape architecture of the urban built environment of the city. This could create solutions for the problem of the lack of open green public spaces and places in the cityof Tripoli.